Bionic Design and Performance of Electrode for Bioelectrical Signal Monitoring. Issue 25 (5th August 2022) - Yuan, Cong; Ji, Keju; Zhang, Qian; Yuan, Peng; Xu, Yilin; Liu, Jing; Huo, Tingwei; Zhao, Jiahui; Chen, Jian; Song, Yi; Long, Yi; Dai, Zhendong
Abstract: Stable adhesion and comfort for long‐term use are the main challenges currently limiting wearable in real‐time health monitoring, especially in disturbed state such as exercise and sweating. Here, A biomimetic microneedles‐based adhesive electrode is designed, which utilizes the mechanical locking of the microneedle array and the adhesion property of the mimic tree frog foot pad microstructures on the rough and wet substrate to synergistically enhance the stable adhesion performance of electrode on the skin surface. This adhesion‐mechanical locking synergistic enhancement effect of the electrode through experiments is verified; the synergistic enhancement mechanism of the electrode is analyzed, and successfully electrocardiograph and electromyogram on human body skin is monitored. The electrode presented here provides a new path to solve the problem of stable signal acquisition under the condition of sweating and exercise, and realizing comfortable, low‐noise, and continuous health monitoring. Abstract : This work focuses on the integration of multiple attachment mechanisms into electrodes, and the analysis of the attachment gain effect achieved by the multimechanisms strategy of bioinspired adhesive material and microneedles. It provides a promising pathway to solve the problem of stable signal acquisition during exercising activities and sweat conditions, realizing smooth and comfortable bioelectrical signal monitoring of the body.